Vestibular Deficits in Neurodegenerative Disorders: Balance, Dizziness, and Spatial Disorientation - Cronin, Thomas; Arshad, Qadeer; Seemungal, Barry M. (Frontiers in Neurology, 2017)
The vestibular system consists of the peripheral vestibular organs in the inner ear and the associated extensive central nervous system projections – from the cerebellum and brainstem to the thalamic relays to cortical projections. This system is important for spatial orientation and balance, both of critical ecological importance, particularly for successful navigation in our environment. Balance disorders and spatial disorientation are common presenting features of neurodegenerative diseases; however little is known regarding central vestibular processing in these diseases. A ubiquitous aspect of central vestibular processing is its promiscuity given that vestibular signals are commonly found in combination with other sensory signals. This review discusses how impaired central processing of vestibular signals – typically in combination with other sensory and motor systems – may account for the impaired balance and spatial disorientation in common neurodegenerative conditions. Such an understanding may provide for new diagnostic tests, potentially useful in detecting early disease whilst a mechanistic understanding of imbalance and spatial disorientation in these patients may enable a vestibular-targeted therapy for such problems in neurodegenerative diseases. Studies with state of the art central vestibular testing are now much needed to tackle this important topic.